Faith Schools and State Education: Church-State Relations and the Development of the 5-14 Religious Education Program in Scotland - Coll, Roisín; Davis, Robert (Catholic Education: A Journal of Inquiry and Practice, 2007)
Public policy questions such as public funding for Catholic schools, the extent of government involvement in private education, and church-state relations in general are not unique to the United States. This article discusses Catholic education in Scotland, which a view to explaining the ongoing need for cooperation and goodwill in church-state relations concerning schools.